(untitled) (AmS-Varia, 2020)
In 2015, the Museum of Cultural History organized a large excavation project in Løten, Hedmark with over 90 sites. During the project both clearance cairns and cairns interpreted as graves were excavated. The field at Skillingstad contained more than 100 cairns, of which approximately 40 were excavated. Although originally thought to be clearance cairns, results obtained over the course of the excavation demanded that this interpretation be reconsidered. In the area surrounding Skillingstad, four smaller cairn fields were also excavated, ranging in size from 4 to 21 cairns. Several of these were associated with small, oval, bowl-shaped fields that overlapped in time with the graves at Skillingstad. The plant macrofossil analyses returned few interesting results, but the cairns containing graves and the clearance cairns differed significantly in their micromorphological results. In addition, there were clear differences in structural organization and the relationship between the cairns in the grave and clearance fields respectively. The burial cairns were spread evenly across the site, built with uniform sized rocks and placed with respect to older monuments such that none of the monuments merged into larger units. In contrast, the clearance cairns were more randomly distributed across the site, sometimes cleared to one side of the field and at other sites in between the cultivated land and pastures. The rocks in these cairns were also more variable in size and often several cairns had grown together over time. We will also share some administrative experiences based on the reinterpretation from clearance cairns to graves at Skillingstad.